WITH ACQUISITION OF MARKET SHARE PT SARI HUSADA YOGYAKARTA - Eryanti, Monica Andriyana; Lastari, SE., MM, Siwi; Darini, M.Si., Dra. Sri (Management, 2010)
The purpose of the study are: 1) To know the sales promotion activities by the company, 2) To determine the effect of sales promotions on the company´s market share. Data analysis methods used are kerelasi product moment r. The results of this study were: 1) The total number of sales promotions for 2000 was Rp 994 033 039, 2) The total number of sales promotion for the year 2001 amounted to Rp 1,201,119,613, 3) The total number of sales promotions for 2002 was Rp 1249 .266.688, 4) The total number of sales promotion for the year 2003 was USD 1,213,073,728 sebasar, 5) The total number of promotional sales for 2004 amounted to Rp 1,197,073,728, 6) level marke share for 2000 was 44%, 7) The level of market share for the year 2001 amounted to 39%, 8) level of market share for 2002 was 39%, 9) level of market share for 2003 is sebesar37%, 10) level of market share to cope 2004 amounted to 40%. Based on the analysis and discussion, PT Sari Husada are: 1) correlation analysis found that sales promotion variables strongly and positively correlated with market share of 0.908, 2) Promotion sales significantly influence marke share of PT Sari Husada, PT Yogyakarta Karen tcount > t-table with p ≤ 0.05 then Ha accepted. Keywords: market share, sales promotion.